a(0)a=a+1
a(n+1)a=a(n)a(n)a…
a(0)(0)a=a(a)a
a(0)(1)a=a(0)(0)a(0)(0)a…
a(0)(a)a=a(1)(0)a
a(n)(a)a=a(n+1)(0)a
a(a)(0)a=a(1)(0)(0)a
a(a)(0)(0)…a=a(1,0)a 共a个
a(1,0)(0)a=a(1,0)a…
a(1,0)(1)a=继续对角化
a(1,0)(a)a=a(1,0)(0)(0)a…
a(1,1)a=a(1,0)(1,0)(1,0)…a共a个
a(1,a)(1,a)…a=a(2,0)
…
a(1,0…)a(a个)=a(1,,(0))a
a(1,,(1))a=a(1,,(0))a(1,,(0))a…
a(1,,(a))a=a(1,,(0)(0))a
a(1,,(0)(1))=a(1,,(0)(0))a…
…
a(1,,(1,,(1,,…=a(2,,(0))a
a(a,,(a,,…)a=a(1,0,,(0))a
a(1,1,,(0))a=a(1,0,,(1,0,,(…
按此规则继续
a(1,a,,(0))…
a(1,,1,,(0))=a(1,,0,,(…
接下来的是对角化就是a(n,,(…不是就是原来的展开
(a,,a,,a,,…)a=a(1,,,(0))a
a(1,,,(1,,,0,,(1,,,0,,(……))))a=a(1,,,1(0))a
…
a(1,,,0,,,(1,,,0……)a=a(1,,,1,,,0)a…后面的都和,,,一样
a(1,,,,,,,…)a=a.((0),1)a 共a个.
这个增长率会有多少
a(n+1)a=a(n)a(n)a…
a(0)(0)a=a(a)a
a(0)(1)a=a(0)(0)a(0)(0)a…
a(0)(a)a=a(1)(0)a
a(n)(a)a=a(n+1)(0)a
a(a)(0)a=a(1)(0)(0)a
a(a)(0)(0)…a=a(1,0)a 共a个
a(1,0)(0)a=a(1,0)a…
a(1,0)(1)a=继续对角化
a(1,0)(a)a=a(1,0)(0)(0)a…
a(1,1)a=a(1,0)(1,0)(1,0)…a共a个
a(1,a)(1,a)…a=a(2,0)
…
a(1,0…)a(a个)=a(1,,(0))a
a(1,,(1))a=a(1,,(0))a(1,,(0))a…
a(1,,(a))a=a(1,,(0)(0))a
a(1,,(0)(1))=a(1,,(0)(0))a…
…
a(1,,(1,,(1,,…=a(2,,(0))a
a(a,,(a,,…)a=a(1,0,,(0))a
a(1,1,,(0))a=a(1,0,,(1,0,,(…
按此规则继续
a(1,a,,(0))…
a(1,,1,,(0))=a(1,,0,,(…
接下来的是对角化就是a(n,,(…不是就是原来的展开
(a,,a,,a,,…)a=a(1,,,(0))a
a(1,,,(1,,,0,,(1,,,0,,(……))))a=a(1,,,1(0))a
…
a(1,,,0,,,(1,,,0……)a=a(1,,,1,,,0)a…后面的都和,,,一样
a(1,,,,,,,…)a=a.((0),1)a 共a个.
这个增长率会有多少